The Role of Marketing Innovation in Household Business Sustainability: A Resource-Based View Approach - Sipahutar, Icha Darlene Hanna; Simanjuntak, Mariana (Dinasti Publisher, 2026)
Marketing innovation has become an important capability that enables household businesses to improve competitiveness and adapt to changing market conditions. Through product innovation, price innovation, promotion innovation, and retail innovation, business actors can create value and strengthen their market position. This study aims to examine the influence of product innovation, price innovation, promotion innovation, and retail innovation on marketing innovation, as well as the effect of marketing innovation on household business sustainability from a Resource-Based View (RBV) perspective. A quantitative approach was employed using a survey of 210 household food business actors in Medan City selected through purposive sampling. Data were collected through a structured questionnaire measured using a seven-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that product innovation, retail innovation, and promotion innovation have positive and significant effects on marketing innovation, while price innovation has no significant effect. Furthermore, marketing innovation does not significantly influence household business sustainability. These findings suggest that product quality, promotional capabilities, and diversified sales channels represent valuable internal capabilities that support marketing innovation. This study contributes to the Resource-Based View literature by providing empirical evidence regarding the role of internal capabilities in fostering marketing innovation among household food businesses.